Exploring novel pharmacological trends: Natural compounds in dry eye disease management - Rák Tibor; Csutak Adrienne (Acta Pharmaceutica)
Dry eye disease (DED) is an ocular condition characterized by altered tear film homeostasis, resulting in symptoms like tear film instability, hyperosmolarity, inflammation, and neurosensory abnormalities. It affects visual acuity and quality of life and is influenced by age, gender, and environmental factors. The first line of treatment consists of dynamically developing artificial tears, gels, and eyelid sprays, which can be supplemented with natural ingredients for enhanced efficacy. Other therapeutic steps include auto-logous serum tears, anti-inflammatory and immunosuppressive eyedrops, or oral tablets. Management also targets Meibomian gland dysfunction and the ocular surface micro-biome. This article explores various therapeutic approaches, including natural compounds and complementary strategies. Natural compounds, such as vitamins, and herbal substances (e.g., trehalose), offer promising benefits in enhancing tear film stability and ocular surface protection. Apitherapeutic products like manuka honey and propolis exhibit antibacterial and anti-inflammatory properties. Additionally, human tissue-derived solutions, such as auto-logous serum tears and amniotic membrane extracts, hold the potential for ocular surface regeneration. Other strategies, including polyherbal eye drops, liposomal eyelid sprays, and microbiome-supporting solutions offer alternative therapeutic avenues. Moreover, patient education, lifestyle modifications, and interdisciplinary collaboration play crucial roles in DED management, emphasizing the importance of holistic care approaches.